Implementation of Religious Values and Their Relevance to Religious Moderation (Study at SMP IT Khoiru Ummah) - Nur Azizah; Karliana Indrawari (AJIS: Academic Journal of Islamic Studies, 2022)
The purposes of the study were to find out the religious values in SMP IT Khoiru Ummah, to find out the values of Religious Moderation at SMP IT Khoiru Ummah, and to find out whether religious values were relevant to the values of religious moderation at SMP IT Khoiru Ummah. This research used a qualitative research type. This research was conducted at SMP IT Khoiru Ummah Curup. The subjects of this research were the principal, teachers, and students. Data collection techniques were observation, interviews, and documentation. Data analysis techniques steps were reducing data, presenting data, and concluding data. The results show that the Religious values had been carried out well. The evidence of the application of religious values was such as applying the values of faith, worship values, moral values, independent values, being orderly in business, keeping time, maintaining lust, and benefiting others. Religious Moderation values had been implemented with the implementation of religious moderation values such as the values of justice, tawazun, I'tidal, tasamuh, musawah, and shura. In addition, religious values were already relevant to the values of religious moderation, such as the values of faith which were relevant to the values of justice, balance, and tolerance, and the value of worship was relevant to the value of balance and the nature of being straight and firm, the moral values that were relevant to straight and firm nature, tolerance, equality (musawah), deliberation (shura), the religious values that were maintained, and their passions that were relevant to the values of straight and firm nature.